Regional differences in unemployment: the case of Croatia - Valerija Botric (European Regional Science Association (ERSA), 2003)
Most transition economies have gone through severe changes in the labour market during the 1990s. Under the previous socialist regime, unemployment was virtually non-existent due to the pronounced job security, which was also accompanied by low labour mobility. Studies indicate that one of the cornerstones of previous system was flourishing latent unemployment. The transition to the market economy was therefore connected with the process of revealing latent unemployment. Not unlike other transitional economies, the first phase of transition in Croatia was marked by strong decrease in the rate of employment and simultaneously rising rate of unemployment, as labour market agents were more influenced by market-oriented philosophy. The policies designed to reduce the unemployment in Croatia so far have been concentrated on the overall number in the country. However, the available data indicates that some regions have persistently higher registered number of unemployed persons throughout the whole periods. The paper investigates whether there are differences in the regional development of unemployment between Croatian regions or whether the national demand and supply conditions predominate region-specific determinants.
Keywords: 330